Social issues in the Czech elementary school curriculum as related to children with specific educational needs and in the context of cooperation with professional institutions - Hřivnová, Michaela; Majerová, Jana (Wydawnictwo Uniwersytetu Rzeszowskiego, 2015)
Since 2007 education in the Czech Republic has followed a new curricular document called the Framework Education Programme for Elementary Education. This document has been amended and reviewed several times, most recently in September 2013. The key competencies that elementary school students should acquire include communicative competency, social and personal competency and civil competency. Their development is also supported by the educational area Man and Health and the educational field Health Education. The specific expected outcomes and content of this field of study include a very wide issue associated with health care in all bio-psycho-social aspects, promotion of healthy lifestyle and elimination of risk factors. They also include personality and social development and social issues including the prevention of risk behaviour and social–pathological phenomena. These issues are addressed both in the context of the education of pupils without specific educational needs and pupils with specific educational needs, e.g. at special schools. In the context of cooperation between educational institutions and professional subjects, particularly primary, but also the secondary and tertiary prevention, involves searching for an optimum solution in the area of risk behaviour or social–pathological phenomena.
Keywords: Framework Education Programme for Elementary Education; key competencies; Health Education; expected outcomes; a pupil with specific educational needs; risk behaviour (social-pathological phenomena); primary prevention; professional institutions